2016
DOI: 10.1177/0022034516657803
|View full text |Cite
|
Sign up to set email alerts
|

Surveys on Reporting Guideline Usage in Dental Journals

Abstract: The objectives of this study were 1) to find out if and how authors and peer reviewers for dental journals are encouraged to use reporting guidelines (RGs); 2) to identify factors related to RG endorsement; and 3) to assess the knowledge, opinions, and future plans of dental journal editors in chief (EICs) on RGs. A total of 109 peer-reviewed and original research-oriented dental journals that were indexed in the MEDLINE and/or SCIE database in 2015 were included. The "instructions to authors" and "instruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 59 publications
5
33
2
Order By: Relevance
“…However, our results revealed progress in the endorsement of RGs. By contrast, a 2015 survey (Hua et al, ) of journal instructions to authors showed that references or recommendations for the use of RGs during reviews were low (55 [50.5%] of 109 journals assessed).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, our results revealed progress in the endorsement of RGs. By contrast, a 2015 survey (Hua et al, ) of journal instructions to authors showed that references or recommendations for the use of RGs during reviews were low (55 [50.5%] of 109 journals assessed).…”
Section: Discussionmentioning
confidence: 96%
“…In 2015, Moher et al () investigated the editorial policies of leading medical journals by focusing on 10 core questions that are related to research waste. A survey of dental journal editors conducted by Hua, Walsh, Glenny, and Worthington () provided thorough information regarding the use of RGs in dentistry. Hence, to our knowledge, whether and to what extent dental journals have adopted editorial policies that can reduce avoidable research waste remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most relevant result of this descriptive study is that the proportion of retracted papers in dentistry is low compared to the biomedical literature indexed in PubMed, as revealed by our exploratory findings. We could suggest some reasons for this: there is a time-lag of at least 3 years in PubMed notices of retraction [20]; the retraction of papers in this field of knowledge is a recent occurrence when compared with the biomedical literature as a whole; inappropriate or fraudulent data can be very difficult to detect [23]; dental journals have been slow to endorse well-recognised reporting guidelines [24] that could facilitate the identification of ethical problems in the manuscripts. Since there is lacking information on this topic in the field of dentistry, it is difficult to discuss the findings of our study within the specific context of the dental literature.…”
Section: Discussionmentioning
confidence: 99%
“…Stevens et al showed that the PRISMA endorsement is associated with more complete reporting . In dentistry, two surveys were conducted investigating the use of reporting guidelines by dental journals and showed that the PRISMA endorsement and implementation is not optimal with considerable room for improvement . Furthermore, the authors of both studies indicated that a broad understanding of the employment of reporting guidelines is necessary by dental journal editors, authors, peer‐reviewers and dental schools/institutions.…”
Section: Resultsmentioning
confidence: 99%
“…53 In dentistry, two surveys were conducted investigating the use of reporting guidelines by dental journals and showed that the PRISMA endorsement and implementation is not optimal with considerable room for improvement. 9,54 Furthermore, the authors of both studies indicated that a broad understanding of the employment of reporting guidelines is necessary by dental journal editors, authors, peer-reviewers and dental schools/institutions. It is not only a matter of using a guideline, but truly incorporating it into research practice so that stakeholders, researchers, clinicians, and patients benefit from the transparency of the process.…”
Section: Use Of Prisma Statementmentioning
confidence: 99%